Disclosure of Fraud Through Forensic Accounting, Audit Investigation and Auditor Professionalism - Riza Amalia Rifani; Hamida Hasan (Jurnal Economic Resource, 2022)
This study aims to analyze the effect of the application of forensic accounting, investigative audits, and auditor professionalism on fraud disclosures at the BPKP office representing the province of South Sulawesi. This study used primary data by conducting direct research in the field by providing questionnaires to 35 auditors from the BPKP office representing South Sulawesi Province. The statistical method used is multiple linear regression analysis with the help of SPSS software. The results of the analysis showed that forensic accounting variables had a positive and significant effect on fraud disclosure, investigative audit variables had a positive and significant effect on fraud disclosure, and auditor professionalism had a positive effect on fraud disclosure.